Fetal dose estimation for Virtual Tangential-fields Arc Therapy whole breast irradiation by optically stimulated luminescence dosimeters. (September 2022) - Dusi, F.; Guida, F.; Garcia, E.N. Villegas; Rossato, M.A.; Germani, A.; Sapignoli, S.; Scaggion, A.; Scott, A.; Zorz, A.; Paiusco, M.
Highlights: This work is the first investigation on fetal dose with ViTAT plan for breast RT. 6XFFF ViTAT can be used in place of 3DCRT while maintaining similar fetal dose. Custom OSLD out of field calibration is needed to avoid errors up to 30%. Abstract: Breast cancer is the most frequently diagnosed tumor in pregnant women and radiation therapy should carefully be weighted up because of the dose to the fetus. The aim of this study was to investigate fetal dose in a patient treated with Virtual Tangential-fields Arc Therapy (ViTAT), an innovative technique for whole breast irradiation. Optically stimulated luminescence detectors (OSLDs) were calibrated on a Varian TrueBeam linac, with both a 6X and 6XFFF beam quality, and used for out-of-field measurements. Fetal dose related with ViTAT technique was compared to the standard 3D conformal radiation therapy technique (3DCRT). The fetal dose delivered with a ViTAT technique planned with 6XFFF beam was also investigated. Measurements were taken on a phantom composed of Rando Alderson Phantom slices and solid water slabs. OSLDs were placed in a region identified by the height of the fundus from conception to the twentieth week using a custom made PMMA grid. Due to the higher number of monitor units, the peripheral dose of ViTAT delivered with 6X beams is higher than that of 3DCRT. However, nanoDots measurements prove that ViTAT can be used in place of 3DCRT while maintaining similar fetal dose levels if 6XFFF beams are used.